Knowledge and Practice of Burn First Aid Among Saudi Arabian Medical and Non-Medical University Students. (July 2021) - Batais, Mohammed A.; Alzahrani, Sultan A.; Alzahrani, Nawaf A.; Alsolimi, Abdulaziz F.; Khan, Anas A.; Aldossari, Khaled K.; Al-Zahrani, Jamaan M.; Alghamdi, Talal; Almigbal, Turky H.
Burns are serious injuries, resulting in high morbidity and healthcare costs. Effective first aid improves outcomes. The aim of this study was to assess the knowledge and practice of first aid for burn injuries among medical and non-medical students in Saudi Arabia. A cross-sectional study (N = 408) was conducted, in which a questionnaire was administered assessing students' experience with burns, as well as their hypothetical responses to vignettes involving patients with burn injuries. Although most students reported having personal experience with burns, and had received some information regarding burn first aid, only about half were able to provide correct responses regarding first aid techniques, and medical students were no more accurate than non-medical students in their responses. Results suggest that members of the Saudi Arabian population may lack appropriate knowledge about burn first aid, and education and public information resources may help to remedy this problem.